Spectroscopic photoacoustic/ultrasound/optical-microscopic multimodal intrarectal endoscopy for detection of centimeter-scale deep lesions - Jiang, Jinsheng; Yuan, Chuqi; Zhang, Jiaxi; Xie, Zhuojun; Xiao, Jiaying (Frontiers in Bioengineering and Biotechnology, 2023)
The inadequacy of existing colorectal imaging tools has significantly obstructed the efficient detection of colorectal cancer. To address this issue, this work presents the cross-scale endoscopic imaging of rectal tumors with a combined photoacoustic/ultrasound tomography system and wide-field optical microscopy. This multimodal system combines the merits of centimeter-scale deep penetration, multi-spectral imaging, cross-scale imaging ability, low system cost, and 360º view in a single modality. Results indicated that the proposed system could reliably depict the location of the cancer invasion depth spectroscopically with indocyanine green (ICG). The tumor angiogenesis can be well identified in the wide-field optical imaging mode, which helps to localize the tumors and guide the following photoacoustic/ultrasound scan. This work may facilitate the accurate characterization of colorectal cancer and promote the clinical translation of photoacoustic-based colorectal endoscopy.